AN ASSESSMENT OF PREPARATION LEVEL, SURVIVAL SKILLS, AND ENTREPRENEURIAL KNOWLEDGE AMONG RETIRED TEACHERS IN ZAMBIA - Robinson Mambwe; Chisha Mwape (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2017)
This study investigated the preparation level, survival skills, and entrepreneurial knowledge among retired teachers in Zambia, as well as the success of their post-retirement business ventures. Descriptive survey design utilising both quantitative and qualitative methods were employed through use of questionnaires and semi-structured interviews. Convenient and purposive sampling techniques were utilised in sampling. The conclusion shows that most retired teachers lack survival and entrepreneurial skills to manage their business ventures. Lack of pre-retirement entrepreneurial training, lack of pre-retirement counselling, and poor planning for retirement life were found to be the major hindrances to retired teachers' success in managing their business ventures. The article points to the need for major reforms in teacher training and in pensions scheme policies in Zambia to accommodate issues of financial literacy and entrepreneurial skills among teachers as a way of preparing teachers and other civil servants for life after formal employment.